Enhancement of resistant starch content in modified rice flour using extrusion technology. Issue 3 (12th February 2021) - Gulzar, Beenish; Hussain, Syed Zameer; Naseer, Bazila; Naik, Haroon Rashid
Abstract: Background and objectives: The present study was conducted with an aim to modify rice flour for enhancement of resistant starch content using extrusion technology. The effects of feed moisture, barrel temperature, and screw speed on resistant starch (RS), predicted glycemic index (pGI), glycemic load (GL), and instrumental color ( L *, a *, and b * values) were investigated using response surface methodology. Findings: RS, pGI, GL, L *, a *, and b * varied between 4.91%–6.83%, 73.20–76.90, 48.0–53.04, 70.43–85.95, 6.92–10.32, and 15.09–30.81, respectively. Models obtained for these parameters were highly significant ( p  ≤ .0028). Significantly ( p  < .05) higher RS content (6.20%) and lower pGI and GL values (75.10 and 50, respectively) were recorded in modified rice flour (MRF) as compared to native rice flour (NRF). Lower values of pasting properties and higher thermal properties were recorded in MRF than NRF. Scanning electron micrographs showed continuous and dense network structures in MRF, whereas ungelatinized granules were evident in NRF. Conclusion: Extrusion processing caused significant changes in the digestibility of rice flour which increased the RS content and decreased the pGI in MRF. 30% moisture content, 140°C barrel temperature, and 70 rpm screw speed were found most feasible conditions to enhance RS content in MRF. Novelty: The extrusion of rice flour without a die proved to be a unique way to produce pregelatinized rice flour with higher RS and lower pGI. MRF can be explored for development of functional foods especially for diabetic and celiac disease patients.